Application of the Virtual Laboratory Assisted Inquiry Learning Model for Understanding the Concept of Light Theory and Optical Instruments for Class VIII Students of SMPN 24 Bekasi - Amalillah, Firda Desilia; Susanti, Laily Yunita (UIN Fatmawati Sukarno Bengkulu, 2021)
IJIS Edu : Indonesian J. Integr. Sci. Education, 3 (2), 2021Copyright © 2021, IJIS Edu : Indonesian Journal of Integrated Science Education 175Application of the Virtual Laboratory Assisted Inquiry Learning Model forUnderstanding the Concept of Light Theory and Optical Instruments forClass VIII Students of SMPN 24 Bekasi.Firda Desilia Amalillah1 , Laily Yunita Susanti21,2 Tadris IPA, Fakultas Tarbiyah dan Ilmu Keguruan, UIN KHAS Jember, IndonesiaCoressponding Author. E-mail:2 susantilaily89@gmail.comReceived: May 24th, 2021 Accepted: July 6th, 2021 Online Published: July 7th, 2021AbstractLight material and optical equipment are materials that have conceptual and procedural characteristics sothat they require practical activities, but this practicum is still rarely carried out due to the limitations oflaboratory equipment and materials, the availability of school facilities and infrastructure that are notadequate In the learning process the teacher uses learning media, namely power points and learning videosthat are delivered using the lecture method. This study aims to determine the effect of the application ofthe guided inquiry learning model assisted by the Virtual Laboratory on the understanding of the conceptof light material and optical instruments for class VIII SMPN 24 Bekasi. To identify these problems,researchers using a quasi-experimental method (quasi-experimental), with a nonequivalent control groupdesign. This study obtained the result that the guided inquiry learning model with the help of virtuallaboratory media had an effect on increasing the ability to understand the concept of light and opticalinstruments. This is indicated by a significant increase in students' ability to understand science concepts,oral communication, collaboration, and problem-solving after following the guided inquiry learningprocess with the help of virtual laboratory media with an average of 8.49 in the experimental class while inthe control class 7.91